Using Vygotsky’s sociocultural theory to explore ethnic cultural representation in Taiwanese preschool children’s play - Chen, Bi-Ching (Frontiers in Education, 2025)
IntroductionThis research aims to understand how preschool children in Taiwan, where ethnic integration is common, incorporate their unique ethnic and cultural backgrounds into their play activities to express and integrate their cultural identities. Using Vygotsky’s sociocultural theory as a theoretical lens, the study examines and analyzes these attributes.MethodsThis study employed purposive sampling to select a public preschool in Taoyuan City, Taiwan, and adopted a qualitative research approach. The play behavior of 27 Taiwanese children was observed over a two-month period, during which nine interviews were conducted with preschool teachers. Teachers’ reflections on instruction and children’s portfolios were also collected to provide supplementary insights into elements that could not be fully clarified through observation and interviews.ResultsThe analysis was grounded in Vygotsky’s sociocultural theory, and the data were coded to systematically organize and condense the information. The findings revealed the following: (i) Children express their cultural traits through folk festival ceremonies during play activities; (ii) Engaging in play activities related to folk festival ceremonies is essential for these children, as it deepens their understanding of the cultural contexts within their respective ethnic communities. Moreover, the children demonstrate the ability to integrate their knowledge and skills related to the cultural characteristics of their ethnic groups.DiscussionThe play activities of Taiwanese preschool children exhibit a dynamic nature and undergo modifications over time across different ethnic, cultural, and contextual settings, as exemplified by the variety of materials, shapes, flavors, and terms associated with rice dumplings reported by children. Thus, recognizing and addressing cultural diversity within early childhood education settings is essential for promoting meaningful engagement and facilitating children’s successful adaptation to socially diverse environments.